The law and challenges to access medical record for medical negligence claims in Malaysia - Maizatul Farisah Mohd Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Medical records are one of the most essential documents for a plaintiff in medical negligence claims if the plaintiff is the patient. Medical records are used for ‘discovery’ in preliminary proceeding to establish the case which is the cause of action as well as to show negligence and causation during the trial. Medical records provide important information to determine whether a medical practitioner was negligent or not. But patients have no authority to access and keep medical records. The parties who have the authority to keep and access medical records are the medical practitioners (who provide the medical records) and the hospital or clinic, or any other healthcare institute. They have the legal obligation to protect and keep the confidentiality of the medical records. Therefore, plaintiffs must first obtain a court order prior to obtaining their medical record. However, the decision made in the case of Nurul Husna Muhammad Hafiz & Anor v Kerajaan Malaysia & Ors [2015] 1 CLJ 825 has changed the law pertaining to the obtaining a court order for access to medical records. This paper considers medical records for medical negligence claims in court as well as the law governing medical records and the challenges and obstacles faced in obtaining medical records from the perspective of the law on confidentiality. Finally, it also discusses the decision made in the case of Nurul Husna Muhammad Hafiz & Anor v Kerajaan Malaysia & Ors [2015] 1 CLJ 825 which according to the court parties who wish to access medical records for medical negligence claims no longer require an order of a court to do so.